Uso di sostanze nei contesti di divertimento. Strategie metodologiche e di collaborazione con i servizi di Riduzione del Danno - Nistri, Giulia; Lenzi Grillini, Filippo (Antropologia Pubblica, 2024)
This paper focuses on a research consultancy developed in collaboration with harm reduction services. At first, ethnographers were asked to map and analyze tendencies and patterns of recreational drug use within different types of contexts (clubs, free parties, festivals, pubs, etc.) located in eight Italian territories. But, almost immediately, the negotiation with the sponsor brought researchers to include also an analysis of the relationship between services and “consumers”. Due to limited funds and time available to carry out the consultancy, and considering the heterogeneity of fifieldwork, ethnographers had to look for alternative ways to reach and include a higher number of substance consumers. To face this challenging field researchers developed creative, unusual strategies and (perhaps unorthodox) methods. The outcome of the consultancy permitted us to analyze the peculiar methodologies characterizing harm reduction services and their relationship with consumers. Furthermore, the researchers managed to capture some features of the consumers’ strategies and habits within loisir contexts. Despite the limits of the chosen research strategies, the partnership revealed interesting perspectives on harm reduction for both operators and ethnographers.